2024
DOI: 10.1039/d4cc00290c
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas systems combined with DNA nanostructures for biomedical applications

Shujuan Sun,
Haoqi Yang,
Ziyong Wu
et al.

Abstract: DNA nanostructures are easy to design and construct, have good biocompatibility, and show great potential in biosensing and drug delivery when combined with CRISPR/Cas systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 130 publications
0
1
0
Order By: Relevance
“…6 The biosensing approach uses biologically active biomolecules, such as enzymes, antibodies and nucleic acids, as molecular recognition elements that have high selectivity for the specific target. 7 Fortunately, aptamer-based biosensing (aptasensing) methods for the detection of 5-HT are progressively advancing. In 2018, Nakatsuka et al pioneeringly reported an aptasensing strategy for the determination of 5-HT using field effect transistors based on target-induced aptamer conformational changes.…”
mentioning
confidence: 99%
“…6 The biosensing approach uses biologically active biomolecules, such as enzymes, antibodies and nucleic acids, as molecular recognition elements that have high selectivity for the specific target. 7 Fortunately, aptamer-based biosensing (aptasensing) methods for the detection of 5-HT are progressively advancing. In 2018, Nakatsuka et al pioneeringly reported an aptasensing strategy for the determination of 5-HT using field effect transistors based on target-induced aptamer conformational changes.…”
mentioning
confidence: 99%